2004
DOI: 10.1038/sj.onc.1208298
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and prognostic distinction between serous ovarian carcinomas of varying grade and malignant potential

Abstract: Profiles of gene transcription have begun to delineate the molecular basis of ovarian cancer, including distinctions between carcinomas of differing histology, tumor progression and patient outcome. However, the similarities and differences among the most commonly diagnosed noninvasive borderline (low malignant potential, LMP) lesions and invasive serous carcinomas of varying grade (G1, G2 and G3) have not yet been explored. Here, we used oligonucleotide arrays to profile the expression of 12 500 genes in a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
125
3
11

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(149 citation statements)
references
References 58 publications
10
125
3
11
Order By: Relevance
“…Gene expression of epithelial ovarian cancer C Le Page et al Interestingly, our LMP tumours showed the least distinct profile in comparison to NOSE (Figure 1), which correlates with the weak aggressive potential of these tumours and the favourable prognostic for the patient. The present results correlate well with recent attempts to distinguish LMP and solid malignant tumours using a microarray and gene profiling approach (Gilks et al, 2005;Meinhold-Heerlein et al, 2005;Ouellet et al, 2005). Here, we detected only a very small set of genes differentially expressed in LMP tumours.…”
Section: Discussionsupporting
confidence: 91%
“…Gene expression of epithelial ovarian cancer C Le Page et al Interestingly, our LMP tumours showed the least distinct profile in comparison to NOSE (Figure 1), which correlates with the weak aggressive potential of these tumours and the favourable prognostic for the patient. The present results correlate well with recent attempts to distinguish LMP and solid malignant tumours using a microarray and gene profiling approach (Gilks et al, 2005;Meinhold-Heerlein et al, 2005;Ouellet et al, 2005). Here, we detected only a very small set of genes differentially expressed in LMP tumours.…”
Section: Discussionsupporting
confidence: 91%
“…Although a number of key molecules implicated in control of this vesicle transport chain, including DLK1 and MAP3K5, seem to be up-regulated in LMP tumors (versus highgrade invasive), the pathway has been mostly studied in the context of neuronal transport and axonal damage repair (64,65), and its relation to tumor pathobiology has not been explored. A high incidence of activating mutations in the RAS-MAPK pathway has commonly been found in LMP tumors (3,7,8,11,12), and we found either BRAF or KRAS mutations in the majority of LMP cases tested (59%, 79 of 134). We found BRAF mutations in 46% of serous LMP.…”
Section: Discussionmentioning
confidence: 83%
“…Overall, the results have suggested that LMP tumors follow a different process of cellular transformation compared with the majority of their invasive counterparts. One striking feature of LMP tumors is the high rate of KRAS and BRAF mutations, both of which are thought to act primarily through the canonical RAS-MAPK (RAS-RAF-MEK-ERK-MAP kinase) pathway (3,7,(10)(11)(12)(13). Furthermore, many serous LMP tumors have been reported to have wild-type p53 and functional p53 signaling (8,14).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that progressive paclitaxel resistance in vitro is associated with increasing IL-6 expression in ovarian cancer cell lines and showed that transfection of IL-6 (a Stat3 activating ligand) into some cell lines induced paclitaxel resistance [7,10]. Recently, several studies have demonstrated that Stat3 is highly activated in high-grade as well as recurrent drug resistant ovarian cancer tumor cells [8,18,22,25]. Constitutive activation of the Stat3 pathway has been shown to confer resistance to chemotherapy-induced apoptosis in epithelial malignancies [2].…”
Section: Introductionmentioning
confidence: 99%